1976
DOI: 10.1103/physrevb.14.1314
|View full text |Cite
|
Sign up to set email alerts
|

Spin waves in dilute ferromagnets: Cluster-Bethe-lattice approach

Abstract: A calculation of the local density of spin-wave states in a dilute ferromagnet is presented. It is based on a Green's-function formulation solved within the cluster -Bethe-lattice approximation. The method is compared with an exact solution for the one-dimensional dilute ferromagnet. We also study clusters of nine atoms in the bcc structure, and clusters of 7, 19, and 27 atoms in the simple-cubic structure. Our study shows: (i) a stability condition for ferromagnetism in agreement with percolation theory; (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Salzberg et al [71] employed a Heisenberg hamiltonian for dilute ferromagnet using the cluster-Bethe-lattice (CBL) approximation [72] to compute the Green function and the density of spin-wave states as a function of spin-wave frequency for several values of p in the range of 0.25 to 1.0 in body-centered cubic and simple-cubic lattices with clusters of various sizes. The utilized CBL method gives a plausible description of localized magnetic excitations but with δ-function type anomalies.…”
Section: Development Of Theoretical Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salzberg et al [71] employed a Heisenberg hamiltonian for dilute ferromagnet using the cluster-Bethe-lattice (CBL) approximation [72] to compute the Green function and the density of spin-wave states as a function of spin-wave frequency for several values of p in the range of 0.25 to 1.0 in body-centered cubic and simple-cubic lattices with clusters of various sizes. The utilized CBL method gives a plausible description of localized magnetic excitations but with δ-function type anomalies.…”
Section: Development Of Theoretical Approachesmentioning
confidence: 99%
“…The utilized CBL method gives a plausible description of localized magnetic excitations but with δ-function type anomalies. These anomalies are attributed (i) to isolated magnetic clusters, which result in localized modes comprising one zero-frequency mode, and to (ii) local excitations within the "bulk" ferromagnet which do not propagate beyond a few atoms due to fluctuations in the local configurations [71]. Salzberg et al showed that T c → 0 as p → p c .…”
Section: Development Of Theoretical Approachesmentioning
confidence: 99%
“…Indeed, for d → ∞ the percolation threshold n c → 1 d that does not coincide with the Bethe expression n B c = 1 2d−1 which is an asymptotic of the percolation threshold at large d. Nevertheless as we can see from the Table I the results for the percolation threshold obtained from (3.19) are better for d = 2 and d = 3 than the ones obtained within the Bethe-lattice approach. One can find some results of the latter approach for the theory of dilute ferromagnets in [10,11,12].…”
Section: Low Concentration Of Nonmagnetic Impuritiesmentioning
confidence: 99%
“…The earlier applications included localization, 3,4 alloys, 5 spin waves, 6,7 and spin glasses. 8 Recently it has been used to investigate properties of the Potts model, 9 the Blume-Capel model, 10 and the Hubbard model.…”
Section: Introductionmentioning
confidence: 99%